Peran Teknologi Digital dan Inovasi dalam Pengembangan Layanan Perbankan Digital: Peluang dan Tantangan di Era Society 5.0 - Al Fahmi, Moh. Dhofir Jenny (Journal of Islamic Finance and Syariah Banking, 2024)
The emergence of digital technology and innovation has made great progress towards the development of digital banking services. Technological advances mean that the banking world now uses technology-based transactions to make transactions with customers easier. This research method uses library research by collecting data and information obtained through various kinds of material contained in the literature (books). By using analytical descriptions with a qualitative approach in processing the sources. The research results show that the role of digital technology and innovation in developing digital banking services is very helpful for easy access for all parties, both from the banks themselves and also for customers. The emergence of digital banking technologies such as ATM technology, E-Banking, SMS Banking, and M-Banking has become a major change in the banking sector's transformation. Opportunities and challenges arise in terms of society, product promotion, products according to society's needs, increased internet use, growth in digital transactions, and technology adoption in the era of society 5.0. Meanwhile, there are challenges in terms of human resources, privacy security, ease of access, and literacy education for the community.